The influence of pragmatic function on children's comprehension of complex because- and if-sentences - Lemen, Heather C. P.; Lieven, Elena V. M.; Theakston, Anna L. (Frontiers in Language Sciences, 2024)
In complex adverbial sentences, the connectives because and if can perform different pragmatic functions (e.g. Content, Speech-Act; Sweetser, 1990), although this is often overlooked in studies investigating children's acquisition of these connectives. In this study, we investigated whether pragmatic variation is responsible for some of the difficulty young children have in understanding because-and if-sentences (e.g. Emerson & Gekoski, 1980), and tested the extent to which patterns of acquisition are related to the cognitive complexity (e.g. Zufferey, 2010) or input frequency (De Ruiter, Lemen, Lieven, Brandt, & Theakston, 2021) of the different pragmatic types. 92 children (aged 3-5; F = 39) and 20 adults (F = 12) took part in a forced-choice picture task where they had to identify correct pictures after hearing Content and Speech-Act because-and if-sentences. Results showed that children were most accurate on the sentence type where cognitive simplicity and input frequency converge (If Content), but this pattern was largely driven by the girls in the study. For response times, children were fastest with the least cognitively complex sentence types. However, for because Speech-Act sentences, there was an inverse relationship between response time and input frequency. Taken together, these findings suggest that neither account (cognitive complexity or input frequency) can fully explain the findings. Instead, we suggest that the relative contributions of both factors are best understood in terms of the relevance of these utterances to children and the precise contexts in which children hear these utterances produced.